Hemingway: ficcionist and reporter - Marchezan, Luiz Gonzaga (ITINERÁRIOS – Revue de Littérature, 2010)
The article studies one of Ernest Hemingways’ short stories and also one of his chronicles, texts supported by one single primary source: the personal account Hemingway reporter was given by a 76-year-old man, in the surroundings of the River Ebro, in one of the Spanish Civil War’s battle fronts. The 1938 short story, Old man at the bridge, constitutes itself from the founding narrative, fi rst present in the article, also dated from 1938, Bombing of Tortosa.